Self-perception of quality of life and identification of alexithymia in failed back surgery syndrome patients - Martins,Marielza Regina Ismael (2017)
ABSTRACT BACKGROUND AND OBJECTIVES: Failed back surgery syndrome is one of the most frequent nosological entities in a Pain Clinic and is characterized by the persistent maintenance of lumbar and/or lower limbs pain complaints in individuals already submitted to lumbar vertebral surgery. This study aimed at evaluating quality of life and at investigating the presence of alexithymia in a sample of individuals with failed back surgery syndrome, in addition to analyzing correlations between pain intensity and symptoms of anxiety and depression. METHODS: This is a descriptive, exploratory, comparative, cross-sectional study with quantitative approach in a sample of individuals with failed back surgery syndrome (G1) (n=38) and a group with low back pain without surgical intervention (G2) (n=42) of a Teaching Hospital Pain Clinic. Participants were evaluated by the Brief Pain Inventory and the Toronto Alexithymia scale. Emotional factors, such as anxiety and depression, were evaluated by Beck scales and quality of life by the generic WHOQOL-BREF questionnaire. RESULTS: There were mean alexithymia, anxiety and depression scores significantly higher for G1 and poorer quality of life in all domains as compared to G2. There were significant correlations between alexithymia and depression (p<0.01) and quality of life (except for the environment domain) and anxiety/depression (p<0.001). CONCLUSION: Results have highlighted the negative impact of frequently under-diagnosed psychological variables on quality of life. A better understanding of these emotional reactions may promote a more effective participation of health professionals.